2016
DOI: 10.1093/hmg/ddv633
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein interferes with the ESCRT-III complex contributing to the pathogenesis of Lewy body disease

Abstract: α-Synuclein (α-syn) has been implicated in neurological disorders with parkinsonism, including Parkinson's disease and Dementia with Lewy body. Recent studies have shown α-syn oligomers released from neurons can propagate from cell-to-cell in a prion-like fashion exacerbating neurodegeneration. In this study, we examined the role of the endosomal sorting complex required for transport (ESCRT) pathway on the propagation of α-syn. α-syn, which is transported via the ESCRT pathway through multivesicular bodies fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 86 publications
(102 reference statements)
0
45
0
Order By: Relevance
“…Several studies report that a-synuclein is secreted by exosomes, small secretory vesicles released via fusion of MVBs with the plasma membrane. [69][70][71][72] Intriguingly, Rab35 was identified as a regulator of exosome secretion in glial cells, 73 and its appearance in PD patients may indicate that it can serve as a biomarker for these vesicles. An alternative explanation for this finding is that Rab35 levels are upregulated by neurons in response to a-synuclein misfolding/aggregation, as part of an intracellular stress response to stimulate a-synuclein clearance and degradation.…”
Section: Rab35 Network In Neurological and Neurodegenerative Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies report that a-synuclein is secreted by exosomes, small secretory vesicles released via fusion of MVBs with the plasma membrane. [69][70][71][72] Intriguingly, Rab35 was identified as a regulator of exosome secretion in glial cells, 73 and its appearance in PD patients may indicate that it can serve as a biomarker for these vesicles. An alternative explanation for this finding is that Rab35 levels are upregulated by neurons in response to a-synuclein misfolding/aggregation, as part of an intracellular stress response to stimulate a-synuclein clearance and degradation.…”
Section: Rab35 Network In Neurological and Neurodegenerative Diseasementioning
confidence: 99%
“…Consistent with this concept, two recent studies by Spencer and colleagues show that a-synuclein is degraded via the ESCRT pathway, and that lentiviral expression of CHMP2B can rescue neurodegeneration in transgenic mice overexpressing a-synuclein. 71,72 Further work to identify the molecules and pathways involved in a-synuclein-mediated toxicity, and the role of Rab35 in its secretion and/or degradation, will help to clarify the relationship between Rab35 and PD pathogenesis.…”
Section: Rab35 Network In Neurological and Neurodegenerative Diseasementioning
confidence: 99%
“…Hence, a probable absence of functional ESCRT‐III components pre‐disposes neuronal cells toward necroptosis dependent neurodegeneration. α‐Synuclein (α‐syn) implicated in Parkinson's disease and Dementia with Lewy body is known to deregulate ESCRT‐III complex proteins, including CHMP4B activity . Hence, it remains to be seen if a direct correlation exists between downregulation of function of the ESCRT‐III components and neuronal death via necroptosis.…”
Section: Linking Escrt Pathway To Cell Death During Neurodegenerationmentioning
confidence: 99%
“…with Lewy body is known to deregulate ESCRT-III complex proteins, including CHMP4B activity. 102 Hence, it remains to be seen if a direct correlation exists between downregulation of function of the ESCRT-III components and neuronal death via necroptosis.…”
Section: α-Synuclein (α-Syn) Implicated In Parkinson's Disease and Dementioning
confidence: 99%
“…Given the important roles played by Rab5 in retrograde endosomal sorting and trafficking, it is not surprising that recent studies have demonstrated that the function and activity of Rab5 is compromised in early phases of AD, as well as in mouse models of Parkinson's disease (PD) . Persistent hyperactivation of Rab5 upsets other endocytic pathways such as late endosomes, lysosomes and autophagy, processes that have all been found to be altered in AD .…”
Section: Introductionmentioning
confidence: 99%